Modelagem computacional da formação de torta de filtração em filtros de manga - Zanete, Hóliver Zambon (2024)
The growing concern about the impacts of atmospheric pollution on the environment has driven the development of efficient technologies for controlling particulate emissions. Among these technologies, bag filters stand out as effective devices for removing particles from gas streams. These filters consist of a set of filter bags, usually made of fabric or felt, that retain solid particles while clean air passes through the filtering medium. As particles deposit on the surface of the filtering medium, they form a layer known as the filtration cake. This cake increases the resistance to airflow, leading to a higher pressure drop in the system. In this context, a detailed understanding of cake formation is essential for the design and optimization of bag filters. In this work, the implementation of a subroutine based on CFD (Computational Fluid Dynamics) was proposed to predict the formation of the filtration cake in bag filters. Darcy’s law was modified to incorporate particle deposition’s effects on the filter media’s surface on its permeability. The developed subroutine was validated against experimental data available in the literature and subsequently applied to a real bag filter. Three different superficial filtration velocities (5, 10, and 15 cm/s) were evaluated. Initially, the simulations were conducted under singlephase flow conditions (without particle injection), allowing for the fluid dynamics analysis at the beginning of the filtration process. Higher filtration velocities resulted in greater pressure drop. Additionally, the effect of the energy equation on the distribution of flow along the filter surface was observed. After the convergence of the single-phase simulations, particles with a diameter of 5,7 µm and a density of 2,79 g/cm3 were injected at a rate of 0,00127 kg/s for 250 seconds. The results indicated that the formation of the cake redistributed the airflow through the bags, promoting uniformity of the flow along the section of the filter element. It was found that the filling of the filtration chamber alters the pressure drop profile at the beginning of filtration and that, after the stabilization of the particle deposition rate, the increase in pressure drop begins to exhibit linear behavior. The identification of preferential zones for cake formation can significantly contribute to the optimization of bag filter designs